PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI SEKOLAH DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMK SWASTA SE-KECAMATAN UMBULHARJO YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of Motivation to Work, School Organisation Culture and Principals’ Leadership Style on Teachers’ Performance at Private Vocational School. This research aims to find out the influence of motivation to work, school organisation culture and principals’ leadership style on teachers performance of private vocational School. The population of this study was all vocational school teachers at SMK Berbudi Yogyakarta, SMK Cipta Bakti Husada Yogyakarta, SMK Koperasi Yogyakarta, SMK Perkebunan MM-25 Yogyakarta. The amount of them is 138 teachers. The researchsample was taken from 103 teachers. Techniques of data collection is by using questionnaires. The sample was taken by using probability sampling technique in the form of random sampling. Toro Yamane formula was used to determine the total of the sample using 95% confident (5% of error standard) which was taken from 138 teachers. The data was normality test, linearity test and multicolinierity tested. Then it was followed by multiple regression and partial analysis. Based on the research it can be concluded that (1) there is a positive and significant influence of motivation to work, school organisation culture and principals leadership style on teachers’ performance, (2) there is a positive and significant influence of motivation to work on teachers’ performance, (3) there is a positive and significant influence of school organisation culture oo teachers’ performance, (4) there is a positive and significant influence of principal leadership style on teachers’ performance at privatevocational school at Umbulharjo district of Yogyakata 2012/2013. The effective contribution of motivation to work on teachers’ performance is 12,32 % and relative contribution is 15,12%, The effective contribution of school organisation culture on teachers’ performance is 52,50 % and relative contribution is 64,41%, The effective contribution of principal leadership style on teachers’ performance is 16,69 % and relative contribution is 20,47%.